Sphingosine-1-phosphate reduces adhesion of malignant mammary tumor cells MDA-MB-231 to microvessel walls by protecting endothelial surface glycocalyx - Zhang, L.; Zeng, M.; Fu, B. M. (Cellular and Molecular Biology, 2017)
Sphingosine-1-phosphate (S1P) is a sphingolipid in plasma that plays a critical role in cardiovascular and immune systems. Endothelial surface glycocalyx (ESG) decorating the inner wall of blood vessels is a regulator of multiple vascular functions. To test the hypothesis that S1P can reduce tumor cell adhesion to microvessel walls by protecting the ESG, we quantified the ESG and MDA-MB-231 tumor cell adhesion in the presence and absence of 1Î¼M S1P, and in the presence of the matrix metalloproteinase (MMP) inhibitor in post-capillary venules of rat mesentery. We also measured the microvessel permeability to albumin as an indicator for the microvessel wall integrity. In the absence of S1P, ESG was ~10% of that in the presence of S1P, whereas adherent tumor cells and the permeability to albumin and were ~3.5-fold (after 30 min adhesion) and ~7.7-fold that in the presence of S1P, respectively. In the presence of the MMP inhibitor, the results are similar to those in the presence of S1P. Our results conform to the hypothesis that protecting ESG by S1P inhibits MDA-MB-231 tumor cell adhesion to the microvessel wall.